Formulasi dan Karakterisasi Kopi Robusta Specialty dan Gula Kelapa Kristal untuk Meningkatkan Mutu Kopi Robusta Lokal - Syska, Kavadya; Istiqomah, Kholifatun; Ropiudin, Ropiudin (abe.fp.unila.ac.id, 2023)
Formulation of specialty robusta coffee added with crystalline coconut sugar is carried out to develop archipelago coffee products. The purpose of this study was to examine the conditions for the production of the best Robusta specialty coffee-crystalline coconut sugar based on physicochemical and organoleptic characteristics. The formulation for specialty robusta coffee crystal coconut sugar uses 3 temperature ranges, namely 60-70 ℃, 70-80 ℃ and 80-90 ℃, and a combination of specialty robusta coffee: sugar 10:0, 9:1, 8:2, 7 :3 g. The analysis carried out included moisture content, pH, yield, and organoleptic tests. The results showed that the highest pH in the specialty robusta coffee:sugar formulation was 7:3, because the more coconut sugar was added to the specialty robusta coffee formulation, the higher the pH obtained. And the yield obtained is mostly produced in the temperature range of 60-70℃. Based on the preference test for color and aroma, it was preferred that without the addition of crystalline coconut sugar, while for the flavor the formulation with the most addition of crystalline coconut sugar was preferred. Keywords: Characterization, Crystal Coconut Sugar, Formulation, Specialty Robusta Coffee, Quality.